A (Re)Construção dos direitos territoriais dos indígenas pelo viés dos novos direitos: aportes do direito fraterno e do pluralismo jurídico - Petry, Franciele Wasem (Universidade do Vale do Rio dos Sinos, 2013)
This dissertation discusses the (re)construction of indigenous land rights in the Brazilian legal scenario, from historical and legal facts of Latin America, which became the stage of European colonization/conquest from the late fifteenth and early sixteenth century. The arrival of European conqueror had several dimensions, but in this dissertation analyzes the expulsion of indigenous peoples from their original territories and the establishment of the other face of Modernity, whose which was based on conquest and colonization of the lands and peoples of Latin America. The Modernity slaughtered the native peoples of Latin America, although since the beginning of colonization has been forecast by the laws of the Brazilian colony that the Indians were the natural owners of their homelands. Advances and setbacks marked the legislative and constitutional history as the Brazilian territorial question, in essence, the indigenous. The change in the relationship of the Brazilian state with the Indians occurred significantly through the effective protection of land in the 90s, with the democratization process of Brazil. Thus, this dissertation is concerned with analyzing the relationship that indigenous people have with their traditional lands and the relevance that the protection of the original rights to the lands traditionally occupied presents for the preservation of their cultures. The objective is to analyze the extent to which the respect for indigenous land rights serves to preserve the cultures and ways of life of these people. This analysis transcended the boundaries of legal discipline, using other areas of knowledge. The different paths taken by this research were concerned to seek elements for understanding which are new indigenous territorial rights in Brazil, which are the features these rights, such as the Brazilian legal system reacts to these rights and what is the perception of indigenous peoples as this matter. In this scenario, the discussion about the right, the land and the territory, both from the example of regional ethnic groups (Guarani, Kaingang and Charrua) as decisions of international human rights was essential to the development of this dissertation.
Keywords: Povos indígenas; Constituição Federal Brasileira de 1988; Terra; Território; Direitos territoriais; Indigenous peoples; Brazilian Constitution of 1988; Land; Territory; Territorial rights; ACCNPQ::Ciências Sociais Aplicadas::Direito